One-of-a-kind production - Tu, Yiliu (Springer, 2011)
Despite the numerous competitive advantages of one-of-a-kind production (OKP), the low efficiency and high costs associated with OKP companies threaten to push their business opportunities into the hands of cheaper overseas suppliers. One-of-a-Kind Production introduces a novel strategy and technology to help OKP companies to efficiently mass-produce customized products. In One-of-a-Kind Production, case studies from OKP companies are used to validate the feasibility and effectiveness of the OKP strategy and technology. These case studies include: a structural steel construction company, a manufacturer of specifically ordered compressors and refrigeration systems, a customized high pressure vessel manufacturing company, and a custom window and door manufacturer. To help readers understand OKP strategy and technology, the authors offer a years free access to the OKP Management and Control Software System. This system is based on a new integrated production control and management concept, namely product production structure. It is a useful tool and One-of-a-Kind Production is a valuable guide for production engineers and managerial staff in manufacturing companies, as well as for university researchers and graduate students.